USAGE OF PROFITABILITY COST METHOD BY SETTING OF UNIVERSAL POSTAL SERVICE OBLIGATION COSTS - Svadlenka, Libor; Salava, Daniel (Doprava a spoje, 2011)
There are specific methods for USO cost determination. The most accurate is the Profitability Cost method, which can be recommended as appropriate for it and could be applied also on conditions of czech postal sector. Nearly all products comprised in USO can be respected as commercially attractive and they would be voluntarily provided by some of market participants undependently on USO.